ADIPOQ polymorphism rs182052 is associated with clear cell renal cell carcinoma. Issue 6 (24th April 2015) - Zhang, Guiming; Gu, Chengyuan; Zhu, Yao; Luo, Lei; Dong, Dahai; Wan, Fangning; Zhang, Hailiang; Shi, Guohai; Sun, Lijiang; Ye, Dingwei
<x xml:space="preserve">Abstract</x> Recent studies have indicated that low circulating adiponectin concentrations are associated with a higher risk of several cancers, including renal cell carcinoma. In this case–control study, we examined the frequency of single nucleotide polymorphisms (rs182052G>A, rs266729C>G, and rs3774262G>A) in the adiponectin gene (ADIPOQ) in 1004 patients with clear cell renal cell carcinoma (ccRCC) compared with a group of healthy subjects (n = 1108). Fasting serum adiponectin concentrations were also examined. Logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (95% CI). The association of serum adiponectin concentration with genetic variants was calculated using a multivariate linear regression model. A significantly higher ccRCC risk was associated with the rs182052 variant A allele (adjusted OR, 1.36 and 95% CI, 1.07–1.74 for AA vs GG, P = 0.013; adjusted OR, 1.27 and 95% CI, 1.04–1.56 for AA vs GG+AG, P = 0.019), and this positive association was more evident in overweight subjects. Fasting serum adiponectin was lower in subjects carrying A alleles of rs182052 in both ccRCC patients (β = −0.399, P = 0.018) and healthy controls (β = −0.371, P = 0.024). These results suggest that ADIPOQ rs182052 is significantly associated with ccRCC risk.